KREDIT-MODULLI SISTEMADA INDIVIDUAL OQIW PROCESSLERIN SHÓLKEMLESTIRIWDIŃ PEDAGOGIKALIQ MEXANIZMIN JETILISTIRIW - Yesemuratov, B. (SCIENCE and SOCIETY, 2023)
This article discusses the credit-module system introduced in the education system of the Republic of Uzbekistan and its importance. At the same time, it is described students’ attitudes and opinions about this system.